Sistem Pakar Diagnosa Penyakit Guillain-Barre Syndrome dengan Menerapkan Algoritma Teorema Bayes - Ita Arfyanti; Muhammad Fahmi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
One of the diseases of the peripheral nervous system is Guillain-Barre Syndrome, this disease usually affects adults aged 30 years and over but does not rule out the possibility of attacking at various ages. This disease usually occurs in someone who has a deficiency of vitamins including B1, B6, B12 and among those who are addicted to alcohol, exposed to poisons and do too many repetitive movements. There are various kinds of symptoms that mark a patient with Guillain-Barre Syndrome including muscle pain, tingling, difficulty swallowing, difficulty breathing, loss of response to motor movements, increased pulse, indigestion, excessive sweating, unstable blood pressure. Then a study was carried out that utilized an expert system with the Bayes theorem algorithm. This system can make it easier for an expert to diagnose the patient's disease easily and more efficiently with the advantage of not having to meet directly between the patient and the doctor. Based on these problems, the researcher applied the algorithm above to produce a diagnosis with a percentage of the possibility that the patient suffered from this disease based on existing symptom data of 77.2%.